Kira-kira - Kadohata, Cynthia (New York : Atheneum Books for Young Readers, 2004)
Chronicles the close friendship between two Japanese-American sisters growing up in rural Georgia during the late 1950s and early 1960s, and the despair when one sister becomes terminally ill.
Keywords: Sisters-fiction; Friendship-fiction; Japanese Americans-fiction; Death-fiction; Georgia-history-20th century-fiction